Pengaruh Kepuasan Kerja dan Komitmen Organisasi terhadap Turnover Intention pada Karyawan Sales Promotion Girl dan Sales Promotion Boy Sogo Departement Store Bigmall Samarinda - Tya Ananda Rahmah; Syahruddin Y (Faculty of Economics and Business Mulawarman University, 2017)
This Research aim to analyze The Effect of Job Satisfaction and Organizational Commitment on Employee Turnover Intention In Sales Promotion Girl and Sales Promotion Boy SOGO Department Store BIGMALL Samarinda. The research sample consisted of 60 respondents. Election Procedure sample uses purposive sampling method. Data analysis techniques in this study using multiple linear regression analysis. Result of Hypothesis testing (1) Job satisfaction have significant negative effect on employee turnover intention Sales Promotion Girl and Sales Promotion Boy of SOGO Department Store BIGMALL Samarinda, the t test values obtained at -5,346 and significant value job satisfaction 0.000 0.05. (2) Organizational commitment have significant negative effect on employee turnover intention Sales Promotion Girl and Sales Promotion Boy of SOGO Department Store BIGMALL Samarinda, the t test values obtained by -3,125 and organizational commitment have significant value 0.003 0.05. Keywords: job satisfaction, organizational commitment, turnover intention.